The HADDOCK2.2 Web Server: User-Friendly Integrative Modeling of Biomolecular Complexes. Issue 4 (22nd February 2016) - van Zundert, G.C.P.; Rodrigues, J.P.G.L.M.; Trellet, M.; Schmitz, C.; Kastritis, P.L.; Karaca, E.; Melquiond, A.S.J.; van Dijk, M.; de Vries, S.J.; Bonvin, A.M.J.J.
Abstract: The prediction of the quaternary structure of biomolecular macromolecules is of paramount importance for fundamental understanding of cellular processes and drug design. In the era of integrative structural biology, one way of increasing the accuracy of modeling methods used to predict the structure of biomolecular complexes is to include as much experimental or predictive information as possible in the process. This has been at the core of our information-driven docking approach HADDOCK. We present here the updated version 2.2 of the HADDOCK portal, which offers new features such as support for mixed molecule types, additional experimental restraints and improved protocols, all of this in a user-friendly interface. With well over 6000 registered users and 108, 000 jobs served, an increasing fraction of which on grid resources, we hope that this timely upgrade will help the community to solve important biological questions and further advance the field. The HADDOCK2.2 Web server is freely accessible to non-profit users athttp://haddock.science.uu.nl/services/HADDOCK2.2 . Graphical Abstract: Highlights: The HADDOCK Web server has been upgraded to use HADDOCK version 2.2. It supports mixed-type molecules, for example, protein–nucleic acid, such as nucleosomes. NMR-based pseudocontact shifts and radius of gyration restraints are included. The multi-body and solvated docking protocol are extended. The HADDOCK Web server counts over 6000 users and has served more than 100, 000 jobs.